Effects of Magnesium addition on corrosion behaviour of Al-Mg composite fabricated using Powder Metallurgy method - Normah Cheman; Mohd Nazree Derman; Nur Maizatul Shima Adzali (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.